Flexural Strengthening of RC Slabs using Near Surface Mounted GFRP bars - Taha, Sama (AUC Knowledge Fountain, 2022)
Glass Fiber reinforced polymers (GFRPs) have been recently successfully used to increase reinforced concrete elements' strength. In general, FRPs have many advantages such as resistance to corrosion, and high strength-to-weight ratio. On the other hand, debonding from concrete may constitute a limitation to using GFRP bars; hence the increase in strength of RC elements strengthened using GFRP bars may be limited by this premature debonding failure mechanism. This study aims to investigate the strengthening effect of GFRP bars on the capacity of RC slabs when subject to flexure loading. The work studies the use of different bonding lengths, diameters and numbers of GFRP bars in strengthening RC slabs. The objective is to show the effect of debonding failure on the capacity of the GFRP strengthened slabs relative to the different variables used. The work presents the details of the adopted experimental investigation and the results of the flexural tests performed on twelve slabs with different variables. These results are adopted to validate the currently available design provisions of the ACI code of practice for using NSM GFRP to strengthen RC slabs. The GFRP bars were added to the slabs using the near surface mounted technique, due to its better advantages over the externally bonded technique. The results of this work demonstrate that the GFRP NSM strengthened slabs experienced a 13% increase in strength with the use of 1 no.8 GFRP bar with 2 m length, a 27% increase in strength with the use of 1 no. 12 GFRP bar with 2 m length and a 48% increase in strength with the use of 1 no. 16 GFRP bar with 2 m length. This is a substantial increase and would be of great impact if used in the repair of projects. The mode of failure for the GFRP bar with 2 m length is mainly found to be due to Flexural failure. Moreover, when checking the slabs strengthened with 2 no.16 GFRP bars with 1.5 m length, even though the mode of failure was due to debonding, there was a 103% increase in strength. Finally, for the slabs strengthened with the use of 1 no. 16 GFRP with length 1 m, which is less than the minimum bonding length specified by the ACI Code, the mode of failure is found to be concrete crushing at the edge of the GFRP bar, and it showed a 38% increase in strength when compared to the control sample. The results unveiled the ability of the GFRP strengthened slabs to enhance the flexural strength using different diameters, number of bars, and bonding lengths. It is recommended to expand on this work in future research work, to both validate the findings of this study as well as achieve better understanding of the use of Near Surface Mounted GFRP bars in structural applications.